Features of organizing and conducting excursions for persons with disabilities - Pokolodna, Mariia; Kornieieva, Snizhana; Kovalenko, Daria (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
Nowadays, for the adaptation and integration of people with disabilities into society, rehabilitation programs are being created, including the socio-cultural, to which the tourist industry belongs, which is inextricably linked with the organization of excursion services. The demand for excursion services among people with special needs is growing, but their availability is very low due to the non-fulfillment of a number of special conditions for excursion services for this contingent of consumers, which determines the relevance of this research topic. The subject of the research in the article is the features of the organization and conduct of excursions for various categories of persons with disabilities. The goal is to highlight and structure the main organizational and methodological recommendations for excursion services for various categories of persons with disabilities. Tasks: to explore the modern realities of providing excursion services to persons with disabilities in the territory of our state; summarize organizational and methodological recommendations for excursion services for people with disorders of the musculoskeletal system, with hyperkinesis (spasticity), with hearing impairment, with visual impairment, and with joint pathology; identify specific requirements for the components of excursion services for people with disabilities. General scientific methods are used: characteristics to describe the current situation in excursion services for persons with disabilities; system analysis and structuring to determine the organizational and methodological features of excursion services for these groups of excursionists. The following results were obtained: based on the analysis, it may be noted that in modern realities in the state museum institutions are most actively involved in excursion services for people with disabilities, and there are practically no excursions in the urban or natural environment; еach category of sightseers - people with disabilities has certain features that must be considered when providing sightseeing services. Conclusions: organizational and methodological recommendations on excursion services for people with disabilities are summarized and characterized, it should be taken into account as recommendations for its further implementation and development.